Quality of work life among public hospital nurses in Sarawak / Frannelya Francis ... [et al.] - Francis, Frannelya; Sham, Fatimah; Alias, Azniah; Abdul Wahab, Siti Munirah; Yusof, Suzana; Johan, Hasmah (Universiti Teknologi MARA Cawangan Sarawak, 2021)
Globally, the quality of work-life (QoWL) of nurses is significantly affected. They are the largest health care groups and the leading front liners in the clinical settings. When the nurse's quality of work life is compromised, the work environment's dynamic changes will also be affected. At current, the focus issues in nursing include excessive workload and poor work conditions. This study aimed to determine the prevalence of quality of work-life among public hospital nurses in Sarawak General Hospital (SGH), Kuching, Malaysia. Methods: Descriptive study with a purposive sampling technique was used in recruiting 461 nurses working at SGH. A composite scale was used for the assessment of QoWL in nurses. Data were collected using adapted questionnaires that focused on nine different areas. The questionnaires were distributed to the nurses via an online survey.